Contributions of eastern thinkers to world civilization - Mamarajabov, G’ayrat; HasanovaSevara, Sevara (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
This article deals with the enormous influence of our civilization on the development of the peoples of the East, Arab culture and Islamic philosophy. The establishment of states in its territory, which gained relative independence from the Arab Caliphate, has reached new heights due to the tolerance of our people. The article also says that our country has become a major center of culture and science in the world. The ninth and twelfth centuries were known as the Eastern Renaissance, during which scholars al-Khwarizmi, Ahmad al-Farghani, Abu Nasr al-Farabi, Ibn Sina, and Abu Rayhan al-Biruni worked in all fields of science